(untitled) (Baghdad Science Journal, 2024)
This study describes the development of an easy, inexpensive, accurate and fast spectrophotometric technique for the determination of 4-ethylphenol. The primary method involves converting 3-nitroaniline to the diazonium salt and then reacting with 4-ethylphenol in an alkaline medium. It is yellow in color and has a maximum absorption at 426 nm. It obeys Beer’s law in a linear range of 5-12 µg mL-1 with a correlation coefficient of 0.9994 and a molar absorptivity 6.0024 x 103 L. mol-1. cm-1. Cloud point extraction was used to quantify trace amounts of phenol using TritonX-114 as a surfactants, and subsequently, a measurement procedure was performed using a UV spectrophotometer. The value of the correlation coefficient was 0.9998, the molar absorbance was 1.04676 × 104 L. mol-1. cm-1and the linear range was 2-11 μg mL-1. The limits of detection and quantification were determined to be 0.42103 and 0.140345 μg mL-1, respectively. The proposed method was successfully used for the determination of phenol in different environmental samples.